PENERAPAN TEKNIK RELAKSASI NAFAS DALAM MEMBERIKAN ASUHAN KEPERAWATAN PADA PASIEN CHEIS PAIN DI RUANGAN IGD RSUD Prof. Dr. H. ALOEI SABOE KOTA GORONTALO - Pipin Yunus; Respi Yolanda Magaribu (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
; Chest pain (chest pain) is a disease caused by various organ disorders, such as the blood vessels of the heart, lungs and digestive organs. Pain or discomfort in the chest (angina pectoris) is the main symptom and the most frequently reported complaint by patients. Angina pectoris is chest pain caused by decreased coronary blood flow to the heart muscle. Method; In making this research, researchers used descriptive methods and case studies. Researchers obtained client data through observation, interviews, physical examinations, and recording. The methods used are assessment, diagnosis therapy, planning, implementation and evaluation. Results; After the researchers carried out nursing actions on subjects I and II that after 1x6 hours of treatment it was found that the pain problem was partially resolved where the patient still felt pain but with a decreased intensity from before, namely patient I had a pain scale of 3 (mild) and increased 3-4 hour naps , night 7-8 hours. Likewise with patient II where the pain scale decreased to 2 (mild) and increased 2-3 hours during the day, 5-6 hours at night. Conclusion; The author concludes that treating chest pain patients using deep relaxation techniques can help reduce patient pain.